Design Strategy For Selecting Appropriate Energy Absorbing Materials and Structures: Data Library and Customised Selection Criteria. (2015) - Fuss, Franz Konstantin; Belbasis, Aaron; van den Hazel, Bennie; Ketabi, Ardalan
Abstract: As current determination of appropriate selection of energy absorbers is tedious and complicated, a data library and design template is developed, which hinges on the maximal energy density to stress ratio. This is the optimum point of any energy absorber, at which most energy is absorbed per unit volume at minimal reaction force per unit area. This optimum point is therefore defined by the optimal energy density and the optimal stress. From the former, the optimum absorber thickness is calculated considering the contact area and actual impact energy. From the latter, the peak deceleration is calculated considering the contact area and mass. Optimum thickness and peak deceleration are compared to the design constraints and unfeasible solutions are excluded. The remaining feasible solutions are ranked based on smallest optimum thickness, peak deceleration or absorber mass. Applications of the design template are exemplified by design cases.